2001
DOI: 10.1038/sj.bjp.0704326
|View full text |Cite
|
Sign up to set email alerts
|

NCX4016 (NO‐Aspirin) has multiple inhibitory effects in LPS‐stimulated human monocytes

Abstract: NCX4016 (2 acetoxy‐benzoate 2‐(2‐nitroxymethyl)‐phenyl ester, NicOx S.A., France) is an anti‐thrombotic agent, chemically related to acetylsalicylic acid (ASA) and able to release NO. We tested the effects of NCX4016 and ASA on the release of the thromboxane (TX) A2 metabolite TXB2, tumour necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), expression and activity of tissue factor (TF) in stimulated, adherent human monocytes. Both ASA and NCX4016 1 – 1000 μmol l−1 dose‐dependently reduced TXB2 concentration, meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
(34 reference statements)
2
29
0
Order By: Relevance
“…19,20 It has been shown that inhibition of cytokine release is associated with cysteine-nitration and inhibition of caspase-I. Therefore, suppression of IL-1␤ and IL-18 processing may explain the antiinflammatory effects of NCX-4016, 19,34 and TF inhibition may contribute to NCX-4016 antiinflammatory activity.…”
Section: Fiorucci Et Al Tissue Factor Inhibition By Ncx-4016mentioning
confidence: 99%
See 4 more Smart Citations
“…19,20 It has been shown that inhibition of cytokine release is associated with cysteine-nitration and inhibition of caspase-I. Therefore, suppression of IL-1␤ and IL-18 processing may explain the antiinflammatory effects of NCX-4016, 19,34 and TF inhibition may contribute to NCX-4016 antiinflammatory activity.…”
Section: Fiorucci Et Al Tissue Factor Inhibition By Ncx-4016mentioning
confidence: 99%
“…This is consistent with previous evidence that ASA and NCX-4016 have similar inhibitory capacities on TX generation when tested in vitro in LPS-stimulated monocytes and ex vivo in thrombin-stimulated platelets. 20,21 The observed reduction in TX metabolite excretion may imply that COX activity is the major target of NCX-4016. However, the reduction in urinary 11-dh-TxB 2 may result also from inhibition of COX-2 expression.…”
Section: Fiorucci Et Al Tissue Factor Inhibition By Ncx-4016mentioning
confidence: 99%
See 3 more Smart Citations